Ex vivo kidney resection in pharmacological cold ischemia followed by orthotopic autotransplantation - A. A. Gritskevich; S. S. P'yanikin; Z. A. Adyrkhaev; Yu. A. Stepanova; V. V. Kazennov; A. E. Zotikov; A. A. Teplov; A. Sh. Revishvili (Трансплантология (Москва))
Introduction. One of the priorities in oncology includes the development of alternative organoprotection treatments for renal cell carcinoma (RCC) of intraparenchymal and central tumor location.Study objective was to develop the method of extracorporeal kidney resection without ureter transection in conditions of pharmacological cold ischemia, followed by an orthotopic autotransplantation for RCC.Materials and methods. The study included 37 patients who had a morphologically confirmed RCC of stage pT1a-T3bN0M0-1G1-3 with intraparenchymal and central tumour location.Results. The mean duration of surgery was 413.97 ± 89.14 minutes. The mean cold and warm ischemia time of kidney was 151.41 ± 41.29 minutes, and 8.39 ± 4.75 minutes, respectively. Intraoperative complications made 8.1% (3), postoperative complication rate was 48.6% (18).Conclusion. Extracorporeal kidney resection without ureter transection in conditions of pharmacological cold ischemia, followed by an orthotopic autotransplantation in RCC allows the resection of large tumors in any location in conditions of prolonged cold ischemia.